MEANING CONFLICT IN HIGHER SCHOOL TEACHER'S ACTIVITY (EXPERIENCE OF EMPIRICAL RESEARCH) - Natalia B. Moskvina (Высшее образование в России)
The article suggests a method to analyze the main aspects of the higher school teacher's professional activity and presents the results of its testing. The basis of the analysis is the ratio of activity aspects distributed on two scales: the subjective significance for a teacher and time expenditure for their implementation. Detection of the most important aspects allows to specify those ones that are filled with personal meaning for teachers. One of the factors that ensures practical implementation of these meanings is time resource needed for the implementation of this or that aspect of the activity. Thus, in teacher's professional activity there can be identified and scaled different areas: from the safe area, where there is no significant discrepancy between importance and time-consuming, to the conflict one, which includes the aspects of activity with a significant gap between two indicators, which mark the presence of a meaning conflict.